Association between maternal usage of volatile organic compounds and West syndrome, the Japan Environment and Children’s study - Hideki Shimomura; Naoko Taniguchi; Tetsuro Fujino; Sachi Tokunaga; Yohei Taniguchi; Takafumi Nishioka; Narumi Tokuda; Masumi Okuda; Masayuki Shima; Yasuhiro Takeshima; The Japan Environment and Children’s Study (JECS) Group (Scientific Reports)
Abstract Multiple etiologies of West syndrome have been reported; however, there are cases of unknown etiologies. Exposure to volatile organic compounds (VOCs) increases the risk of epilepsy; however, their effects on children remain unknown. This study aimed to investigate the association between maternal occupational usage of VOCs and West syndrome development in children. Using data from a cohort of 88,280 children, we extracted children born to mothers who had used VOCs during pregnancy. Based on an epilepsy diagnosis by the age of 2 years, the frequency of usage of VOCs was comparatively analyzed among the following groups: never diagnosed with epilepsy, West syndrome, and other epileptic syndromes. A total of 15, 154, and 88,111 children were categorized into the West syndrome, other epileptic syndrome, and never diagnosed with epilepsy groups, respectively. The odds ratio (OR) for West syndrome development increased with the frequency of permanent marker usage (one to three times a month: OR = 2.58, 95% confidence interval [CI] 0.75–8.90; one or more times a week: OR = 4.34, 95% CI 1.23–15.26). These results suggested an association between maternal occupational frequent usage of permanent marker and West syndrome development in children.